Analisis Proses dan Pelaporan Penerimaan Negara Pembuatan Paspor dan Visa pada Kantor Imigrasi - Farhan Taufiq; Abdul Muttalib; Faidul Adziem (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the process of state revenue from passport and visa services at the Makassar Class I Special TPI Immigration Office and its compliance with applicable regulations, identify obstacles faced by officers in recording and reporting state revenue, and evaluate the effectiveness of the use of technology in supporting reporting that ensures accountability and transparency. This study uses a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and documentation which were then analyzed thematically to obtain a comprehensive picture of the process, obstacles, and use of technology in reporting state revenue. The results of the study indicate that the process of state revenue from passport and visa services has been carried out according to regulations, but there are administrative and technical obstacles in recording and reporting. The use of information technology is quite effective in increasing accountability and transparency in reporting, although further development is still needed.